Cytotoxic evaluation of some new and potent azole derivatives as antimicrobial agents - Zeinab Faghih; Zahra Rezaei; Akram Jamshidzadeh; Zahra Faghih; Naser Heidari; Soghra Khabnadideh (Shiraz University of Medical Sciences, 2017)
Recently use of antifungal drugs in human medicine has been increased, especially with the advent of AIDS epidemic. Despite the growing list of azoles, their clinical value has been limited by their relatively high risk of toxicity and the emergence of drug resistance. Efforts have focused on the development of new, less toxic and more efficacious antifungal agents. We previously described synthesis of some new azole derivatives. We also evaluated all the synthesized compounds for their antifungal activity.  Most of our compounds showed desirable activity against different species of microorganisms. Here we choose thirteen of these compounds, 5 bentriazole derivatives (1a-5a), 5 imidazole derivatives (1b-5b) and 3 triazole derivatives (1c-3c) to evaluate their cytotoxic activities against a human cancer cell line (MCF-7) using colorimetric MTT cytotoxic assay. Their cytotoxic activities were compared to clotrimazole as a positive control. Our results collectively showed that most of our synthesized compounds had less cytotoxicity against MCF-7 compared to clotrimazole.